If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(z + -2) = 27 Reorder the terms: 3(-2 + z) = 27 (-2 * 3 + z * 3) = 27 (-6 + 3z) = 27 Solving -6 + 3z = 27 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 3z = 27 + 6 Combine like terms: -6 + 6 = 0 0 + 3z = 27 + 6 3z = 27 + 6 Combine like terms: 27 + 6 = 33 3z = 33 Divide each side by '3'. z = 11 Simplifying z = 11
| (q-5)x^2-4x-q=0 | | 4w^2-80w+400=200 | | 6ln(x+8)-2ln(x)= | | x^5=-25 | | 4w^2-100w+200=0 | | 6x-2x=21-141 | | 4w-100w+200=0 | | 4w-100+200=0 | | 3n-33n+90=0 | | y^2-10y-4x+33=0 | | y^2-10y+4y+21=0 | | x^2+10x+4y+21=0 | | 28m(3)=3965 | | 65-4x=8x+15 | | 2x+20+4x-20=3x | | ln(-x)=0.111 | | 512x^3-1=0 | | 2x-x^2-10=0 | | 4j+60=400 | | -96=-6(x-15) | | 3(x+3)=2(4-x) | | 7x+2y-10x+5= | | 3(x-4)=2x-6 | | 12x(x-9)=0 | | 2(2x-3)=3(x-10) | | -5X+12=5X^2-12 | | N^3+n^2-6n=0 | | 14-7x=43-14x | | 2n^2+12n+15=-3 | | 2n^2+12n+15=3 | | 2n^2+n-120=0 | | 10x^2n+47xny+42y^2n=0 |